No Evidence for an Association Between Renal Function and Serious Bleeding Events in Patients Treated With Coumarins: A Population-Based Study. Issue 3 (March 2018) - Houben, Eline; Smits, Elisabeth; Overbeek, Jetty A.; Penning-van Beest, Fernie J. A.; Herings, Ron M. C.; van Herk-Sukel, Myrthe P. P.; Teichert, Martina; de Smet, Peter A. G. M.
Background: Although anticoagulation therapy is closely monitored in the Netherlands, coumarin-induced serious bleeding events are still observed. Current literature suggests that renal impairment may contribute to this.Objective: To explore the association between renal function and bleeding events during coumarin treatment.Methods: A nested case-control study was conducted using data from the PHARMO Database Network. Patients hospitalized for a bleeding event during coumarin treatment were selected as cases and matched on sex, birth year, and geographic region to up to 2 controls using coumarins without hospitalization for bleeding. All values of estimated glomerular filtration rates (eGFRs) were selected in the year before index date (case hospitalization date) and compared between cases and controls using logistic regression analyses.Results: In total, 2224 cases were matched to 4398 controls (61% male; mean ± SD age 75 ± 11 and 78 ± 11 years among cases and controls, respectively). Availability of eGFR values was higher among cases compared with controls (mean ± SD eGFR values 4.5 ± 7.1 vs 3.2 ± 5.5), reflected in the significantly shorter time since last eGFR value (at index date, mean ± SD = 2.7 ± 3.0 vs 3.8 ± 3.1 months; odds ratio [OR] = 0.91, 95%CI = 0.89-0.92). No statistically significant difference was found for the mean eGFR value in the year before index date (mean ± SD 65.7 ± 22.8 vs 64.6 ± 20.9 mL/min/1.73 m 2 ; OR per 10 units [95%CI] = 0.99 [0.96-1.02]).Conclusions: No association between renal function and serious bleeding events during coumarin treatment was observed.